Efektivitas Pelayanan Administrasi Kependudukan Melalui Aplikasi Satu Hari Jadi (Sahaja) Online Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kediri - Nada, Annisa Qothrun; Eprilianto, Deby Febriyan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of technology in public services continues to evolve to enhance the efficiency and quality of e-government, particularly in population administration services. The Department of Population and Civil Registration (Dispendukcapil) of Kediri Regency introduced the Sahaja Online application as an innovation to digitalize administrative services. This study aims to describe the effectiveness of population administration services through the Sahaja Online application using a descriptive method with a qualitative approach. The focus of the study refers to the theory of online service quality effectiveness by Sá et al. (2017), which includes management quality, service quality, information quality, and technical quality. Data collection techniques involved interviews, observation, documentation, and literature review. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that the Sahaja Online application is fairly effective in facilitating population administration services. The application demonstrates management in accordance with SOPs, reliable and secure services, clear and up-to-date information, and technical features that ease user access. However, several challenges remain, such as limited human resources, daily service quotas, device accessibility issues, and uneven dissemination of information. Therefore, it is necessary to develop a cross-platform application, enhance the capacity of service personnel, and optimize information dissemination through the involvement of local governments and community leaders.